2018
DOI: 10.1002/ijc.31406
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, alcohol and cancer mortality in Eastern European men: Findings from the PrivMort retrospective cohort study

Abstract: Eastern European men have among the highest cancer mortality rates globally. Prevalence of smoking and alcohol intake in this region is also high. The aim of our study was to calculate population attributable risk fraction (PARF) of cancer deaths from smoking and alcohol in Russia, Belarus and Hungary, and to examine the contribution of these lifestyle factors to differences in male cancer mortality in the three countries. Data were collected as part of the PrivMort retrospective cohort study. Randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A number of studies have demonstrated associations of heavy alcohol consumption with a higher risk of liver cirrhosis, stroke, coronary artery disease, various cancers, and hypertension ( 22 , 23 ). Consistent with previous studies from Linxian, however, we found that alcohol consumption was associated with lower total and cancer mortality, and a nearly significant reduction in heart disease mortality as well.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated associations of heavy alcohol consumption with a higher risk of liver cirrhosis, stroke, coronary artery disease, various cancers, and hypertension ( 22 , 23 ). Consistent with previous studies from Linxian, however, we found that alcohol consumption was associated with lower total and cancer mortality, and a nearly significant reduction in heart disease mortality as well.…”
Section: Discussionmentioning
confidence: 99%
“…The global trends and a development of addictions in the individual countries presented in many domestic and foreign research studies put pressure on creating many multilevel intervention programs. These programs eliminate addictions and decrease health inequalities from the point of geography, age and gender differentiation [22], [43].…”
Section: Discussionmentioning
confidence: 99%
“…These economic differences are caused by higher negative consequences of alcohol consumption in more marginalized and vulnerable populations. In the study, Stefler et al deal with smoking and alcohol consumption impacts on cancer-related mortality [22]. The aim of their study was to calculate the population attributable risk fraction of cancer deaths from smoking and alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Reductions in smoking rates across the rest of the world have been equally slow and somewhat uneven across geographic regions and demographic strata. [34][35][36] Based on these data, a significant fraction of new patients with a diagnosis of HPV+OPSCC both in the United States and around the world is expected to have a history of significant tobacco exposure and this will likely disproportionately impact minority patients with low socioeconomic status.…”
Section: New Opscc Diagnoses Occur In the Context Of A Persistently High Rate Of Tobacco Exposurementioning
confidence: 99%